The potential of the microbiome as a target for prevention and treatment of carbapenem-resistant Enterobacteriaceae infections - Zhang, Lu; Xu, Tinghui; Chen, Wenqian; Chai, Yinying; Wu, Yi; Du, Xinghai (Frontiers in Cellular and Infection Microbiology, 2025)
Carbapenem-resistant Enterobacteriaceae (CRE) present an escalating threat to global health due to their high transmissibility, limited treatment options, and high mortality rates. The gastrointestinal tract serves as both a major reservoir and a transmission hub for CRE, especially under conditions of antibiotic-induced dysbiosis. This review highlights the growing interest in the gut microbiome as a potential target for preventing and managing CRE infections. Building upon the understanding of CRE pathogenesis, we examine how commensal microbiota contribute to colonization resistance through mechanisms such as nutrient competition, spatial niche exclusion, immune modulation, and the production of antimicrobial metabolites. We further discuss microbiome-based therapeutic strategies, including probiotic administration, fecal microbiota transplantation (FMT), and supplementation with short-chain fatty acids (SCFAs), that have shown encouraging results in reducing intestinal CRE colonization. In addition, we explore emerging microbiome engineering approaches, particularly CRISPR-Cas9-mediated systems, which enable the selective elimination of resistant strains while maintaining microbial homeostasis. Current microbiome-based approaches have shown promise in the treatment and prevention of CRE infections, but further research is still needed to clarify their mechanisms, evaluate long-term safety, and determine their effectiveness in different clinical settings. With continued studies and thoughtful integration into existing infection control and antibiotic stewardship practices, these strategies may gradually contribute to a more practical and sustainable way to manage CRE.